1979
DOI: 10.1093/ajcp/72.3.452
|View full text |Cite
|
Sign up to set email alerts
|

Increase of IgA-bearing Peripheral Blood Lymphocytes in Families of Patients with IgA Nephropathy

Abstract: IgA-bearing peripheral blood lymphocytes, serum IgA, urinary sediments and HLA types of patients with IgA nephropathy and members of their families were examined to elucidate whether some familial factors might be related to the development of IgA nephropathy. Ten patients with IgA nephropathy, 31 family members and 36 age-matched healthy persons were examined. All families included certain members with increased amounts of IgA-bearing peripheral blood lymphocytes. The pattern of the emergence of family member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…The disease is characterized by mesangial deposition of polymeric IgA1 (pIgA1), proliferation of mesangial cells, increased synthesis of extracellular matrix, and infiltration by macrophages, monocytes, and T cells (2). Immunoregulatory abnormalities involving IgA1 synthesis in IgAN include overproduction of IgA1 by B lymphocytes in vitro (3,4), increased serum levels of IgA, IgA-containing immune complexes (5,6), and anionic IgA (7), and abnormal glycosylation of the carbohydrate moieties in IgA1 from these patients (8). Five different IgA receptors have been identified in human subjects, including Fc␣R1 or CD89, the polymeric Ig receptor, the asialoglycoprotein receptor, Fc␣/ R, and the transferrin receptor or CD71.…”
mentioning
confidence: 99%
“…The disease is characterized by mesangial deposition of polymeric IgA1 (pIgA1), proliferation of mesangial cells, increased synthesis of extracellular matrix, and infiltration by macrophages, monocytes, and T cells (2). Immunoregulatory abnormalities involving IgA1 synthesis in IgAN include overproduction of IgA1 by B lymphocytes in vitro (3,4), increased serum levels of IgA, IgA-containing immune complexes (5,6), and anionic IgA (7), and abnormal glycosylation of the carbohydrate moieties in IgA1 from these patients (8). Five different IgA receptors have been identified in human subjects, including Fc␣R1 or CD89, the polymeric Ig receptor, the asialoglycoprotein receptor, Fc␣/ R, and the transferrin receptor or CD71.…”
mentioning
confidence: 99%
“…The cell suspension recovered at the interface was resuspended in RPMI 1640 (Eurobio, Paris, France) and supplemented with penicillin (100 U/ml), streptomycin (100 ,ug/ml), glutamine (2 mM) and 10% heat-inactivated fetal calf serum (FCS). PBMC at a concentration of 2 x 106 cells/ ml were stimulated with pokeweed mitogen (PWM), 5 (Fig. la).…”
Section: Patients and Methods Igan Patientsmentioning
confidence: 99%
“…Although systematic screening urinalysis testing in family members of patients with glomerulonephritis is not a common practice for nephrologists, in the last few years many investigators have reported the occurrence of IgAN or the presence of persistent microscopic haematuria and/or proteinuria in family members of patients with this disease [5][6][7][8][9]. Therefore, two forms of disease have been identified as follows: (i) familial IgAN, characterized by the presence of the disease in siblings or other first-degree relatives; (ii) sporadic IgAN, occurring only in one member of the family [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunological abnormalities that mimic those found in patients have been described in their healthy relatives [20][21][22][23][24]. From our recent investigations [9,10,[25][26][27], we hypothesized that the immunoregulatory defect that underlies the disease might be, at least partially, genetically determined, and that the immune background described in patients should in some way appear in the familial background.…”
Section: Introductionmentioning
confidence: 99%